2010
DOI: 10.1246/cl.2010.456
|View full text |Cite
|
Sign up to set email alerts
|

Direct Decomposition of NO on C-type Cubic Rare Earth Oxides Based on Y2O3

Abstract: C-type cubic (Y 0.99¹x Tb x Ba 0.01 ) 2 O 2.99+¤ (0¯x¯0.4) catalysts were prepared by coprecipitation. The NO decomposition activities at 1173 K were higher than that of (Gd 0.7 Y 0.26 -Ba 0.04 ) 2 O 2.96 reported previously. The highest catalytic activity was obtained for (Y 0.69 Tb 0.3 Ba 0.01 ) 2 O 2.99+¤ , and 100% NO conversion into N 2 and O 2 was realized at 1173 K on this catalyst. Furthermore, the conversion ratio was maintained as high as 70.8% even in the presence of 5 vol % oxygen.The emission of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…It should be noted that this temperature and the W/F value are much lower than those reported for other catalysts to obtain the same NO conversion [24][25][26][27][28] [28] catalysts were reported to exhibit *12%, *13%, \15%, *10%, and *5% NO conversion to N 2 , respectively, at 600°C under W/F of 3.0 g s mL -1 . On the other hand, ST-2(Ce 0.8 Mn 0.15 Ba 0.05 O x ) exhibited 45% NO conversion to N 2 under the same reaction conditions (Fig.…”
Section: Phases Detected By Xrdmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that this temperature and the W/F value are much lower than those reported for other catalysts to obtain the same NO conversion [24][25][26][27][28] [28] catalysts were reported to exhibit *12%, *13%, \15%, *10%, and *5% NO conversion to N 2 , respectively, at 600°C under W/F of 3.0 g s mL -1 . On the other hand, ST-2(Ce 0.8 Mn 0.15 Ba 0.05 O x ) exhibited 45% NO conversion to N 2 under the same reaction conditions (Fig.…”
Section: Phases Detected By Xrdmentioning
confidence: 98%
“…Catalysts, such as precious metals [12][13][14], single metal oxides [15,16], Cu-ZSM-5 [17][18][19], alkali-doped Co 3 O 4 [20,21], perovskites [22][23][24][25][26], C-type cubic rare earth oxides [27,28], and Ba 0.5 /BaY 2 O 4 [29], have been found to be effective for direct decomposition of NO. We found that Ba-Ce-Co mixed oxides prepared by a polymerized complex method showed high NO decomposition activities [30].…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, our research group has focused on the development of C‐type cubic rare earth sesquioxides, R 2 O 3 (R: rare earths), as novel catalysts for direct NO decomposition 710. At temperatures below approximately 2000 °C, three crystal polymorphs of rare earth sesquioxides are known to exist depending on the ionic size of the respective rare earth elements: A‐type hexagonal, B‐type monoclinic, and C‐type cubic (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] At temperatures below approximately 2000°C, three crystal polymorphs of rare earth sesquioxides are known to exist depending on the ionic size of the respective rare earth elements: A-type hexagonal, B-type monoclinic, and C-type cubic ( Figure 1). [11] Among these, the C-type represents a cubic bixbyite-type structure, which the coordination environments of the rare earth cations within each crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice volume of the C-type structure is larger than those of A-type and B-type structures and thus it possesses large interstitial open spaces, which have been found to play an important role during direct NO decomposition in our previous studies. [7][8][9][10] In particular, a C-type cubic (Y 0.69 Tb 0.30 Ba 0.01 ) 2 O 2.99+δ catalyst, in which the Y 3+ sites are partially substituted with Tb 3+/4+ and Ba 2+ , can realize 100 % NO decomposition into N 2 and O 2 at 900°C. [7] To date, however, there have been no systematic studies concerning the fundamental factors associated with pure rare earth oxides (REOs) that exhibit direct NO decomposition activity, and the crucial role of the crystal structure with regard to NO decomposition remains unclear.…”
Section: Introductionmentioning
confidence: 99%